2021
DOI: 10.3390/antiox11010061
|View full text |Cite
|
Sign up to set email alerts
|

Saracatinib, a Src Tyrosine Kinase Inhibitor, as a Disease Modifier in the Rat DFP Model: Sex Differences, Neurobehavior, Gliosis, Neurodegeneration, and Nitro-Oxidative Stress

Abstract: Diisopropylfluorophosphate (DFP), an organophosphate nerve agent (OPNA), exposure causes status epilepticus (SE) and epileptogenesis. In this study, we tested the protective effects of saracatinib (AZD0530), a Src kinase inhibitor, in mixed-sex or male-only Sprague Dawley rats exposed to 4–5 mg/kg DFP followed by 2 mg/kg atropine and 25 mg/kg 2-pralidoxime. Midazolam (3 mg/kg) was given to the mixed-sex cohort (1 h post-DFP) and male-only cohort (~30 min post-DFP). Saracatinib (20 mg/kg, oral, daily for 7 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 161 publications
(203 reference statements)
3
30
1
Order By: Relevance
“…It is well established that epilepsy is associated with abnormal regulation and excessive proliferation of glial cells ( Vezzani et al, 2015 ). Our previous studies and others’ studies have demonstrated that DFP-induced epilepsy is also characterized by neuroinflammation and neurodegeneration ( Gage et al, 2021a ; Gage et al, 2021b ; Guignet et al, 2019 ; Putra et al, 2020a ). Reactive astrogliosis exists on a spectrum ranging from hypertrophy of astrocytes and progressing into the formation of a glial scar ( Sofroniew, 2005 ; Pekny and Pekna, 2016 ).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…It is well established that epilepsy is associated with abnormal regulation and excessive proliferation of glial cells ( Vezzani et al, 2015 ). Our previous studies and others’ studies have demonstrated that DFP-induced epilepsy is also characterized by neuroinflammation and neurodegeneration ( Gage et al, 2021a ; Gage et al, 2021b ; Guignet et al, 2019 ; Putra et al, 2020a ). Reactive astrogliosis exists on a spectrum ranging from hypertrophy of astrocytes and progressing into the formation of a glial scar ( Sofroniew, 2005 ; Pekny and Pekna, 2016 ).…”
Section: Discussionmentioning
confidence: 90%
“…Prior to MDZ, animals were scored on each minute for seizure stage based on a modified Racine scale ( Racine, 1972 ) as described in our previous publications ( Putra et al, 2020b ; Gage et al, 2021b ; Sharma et al, 2021 ). Stage one was characterized by salivation, lacrimation, urination, defecation, and mastication, while stage two was characterized by head nodding and tremors.…”
Section: Methodsmentioning
confidence: 99%
“…The source of the DFP was from the same company (Sigma Aldrich, United States ) for all our experiments, but the batches were different. In our previous studies, female rats always received higher doses than males to achieve a similar SE severity ( Gage et al, 2020 ; 2021a ; 2021b ; 2022a ). In this study, we also used the DFP from different batches but the same vendor as our previous studies.…”
Section: Discussionmentioning
confidence: 87%
“…Saracatinib is an Src inhibitor that also inhibits Fyn, c-Yes, Lyn, BLK, FGR, and Lck and has been shown to reduce glial hyperplasia, neurodegeneration, and nitro-oxidative stress [ 96 ]. On123300 is a multi-target kinase inhibitor that inhibits CDK4, ark5/nuak1, PDGFR, FGFR1, RET (c-RET), and Fyn.…”
Section: The Potential Of Fyn As a Therapeutic Target For Strokementioning
confidence: 99%
“…Preclinical studies in rodents with Fyn inhibitors suggest that targeting this kinase family may be beneficial in humans to prevent ischemic brain injury (Table 1 [95]. Saracatinib is an Src inhibitor that also Fyn, c-Yes, Lyn, BLK, FGR, and Lck and has been shown to reduce glial hyperplasia, neurodegeneration, and nitro-oxidative stress [96]. On123300 is a multi-target kinase inhibitor that inhibits CDK4, ark5/nuak1, PDGFR, FGFR1, RET (c-RET), and Fyn.…”
Section: The Potential Of Fyn As a Therapeuticmentioning
confidence: 99%